Membaca Masa Depan Islamic Science: Komparasi Pemikiran Ziauddin Sardar dan Pandangan Intelektual Muslim Indonesia - Delfi Yatri; Ismail Syakban; Julhadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The discourse on Islamic Science remains a crucial endeavor in deconstructing the dominance of secular Western epistemology. This article aims to compare the thought of Ziauddin Sardar the pioneer of the Ijmali school who emphasizes value-laden science and futures studies with the mapping of views held by Indonesian Muslim intellectuals. Using a qualitative descriptive-comparative method through library research, this study analyzes how foundational Islamic principles such as Tawhid (the unity of God), the limits of knowledge, and the realities of modern science (e.g., quantum mechanics) are addressed by both subjects. The findings indicate that while Sardar operates on a macro-epistemological level and systemic ethics, Indonesian Muslim intellectuals tend to adopt a pragmatic-integrative approach, embedding Islamic values directly into the curriculum and institutional frameworks of modern science. This comparison opens a new space for dialogue on how the future of Islamic Science can be concretely realized without falling into past romanticism or a blind rejection of Western science